2009
DOI: 10.1183/09031936.00074309
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate elevation of N-terminal pro-brain natriuretic peptide in scleroderma-related pulmonary hypertension

Abstract: N-terminal pro-brain natriuretic peptide (NT-proBNP) is a marker of neurohormonal activation that is useful in the diagnosis and prognosis of various forms of pulmonary arterial hypertension (PAH). We sought to characterise and compare NT-proBNP in a cohort of PAH related to systemic sclerosis (PAH-SSc) and idiopathic PAH (IPAH) patients.NT-proBNP levels, collected from PAH-SSc and IPAH patients followed prospectively, were compared and correlated with haemodynamic variables. Cox proportional hazard models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 60 publications
9
98
0
3
Order By: Relevance
“…We did not exclude subjects with interstitial lung disease in this study, which could have been a potential confounder. Finally, Mathai et al 25 recently reported that levels of NT-proBNP predicted survival in subjects with SSc-PAH, but not in those with IPAH. We did not find the same predictive strength for NT-proBNP in our study, possibly because of the larger number of subjects in the Mathai study.…”
Section: Discussionmentioning
confidence: 97%
“…We did not exclude subjects with interstitial lung disease in this study, which could have been a potential confounder. Finally, Mathai et al 25 recently reported that levels of NT-proBNP predicted survival in subjects with SSc-PAH, but not in those with IPAH. We did not find the same predictive strength for NT-proBNP in our study, possibly because of the larger number of subjects in the Mathai study.…”
Section: Discussionmentioning
confidence: 97%
“…We evaluated the relationship between serum ES and clinical markers of exercise performance and function, specifically 6 MWD and NYHA-FC, and serum chemistries previously linked to outcomes in PAH, notably NT-proBNP (18)(19)(20), creatinine (21), and serum sodium (22) ( Table 2).…”
Section: Serum Endostatin Correlates With Clinical Markers Of Diseasementioning
confidence: 99%
“…In 2006, Williams MH et al found that plasma NT-proBNP level was significantly higher in PAH patients associated with systemic sclerosis (PAH-SSc) compared with the SSc patients without PAH [17]. Recently, Mathai SC et al also found that plasma NT-proBNP level was significantly higher in PAH-SSc compared with idiopathic PAH (IPAH) patients and was a stronger predictor of survival in PAH-SSc than IPAH [18]. The results of Mathai's group suggested that the expression of NT-proBNP might be different in the different kinds of PAH.…”
Section: Discussionmentioning
confidence: 99%